Media Pengembangan Flip Chart (Smart Pocket Book) “Organ Pencernaan Hewan Dan Manusia” Mi Al-Husna Tenjolaya Kelas V - Nuraeni, Ein; Lestari, Hana (Institut Agama Islam Sahid (INAIS) Bogor, 2023)
This research was informed by the issue that some students still have not been involved in science learning with class V material about the digestive systems of animals and humans. In fact, MI teachers have used learning media in the form of make-a-math in the classroom as part of the learning process, but they have limited time to teach and inadequate facilities. This study aims to develop a flip chart media (smart pocketbook) for science learning to increase student learning activities towards the material of digestive organs science in humans and animals. TENJOLAYA MI AL HUSNA. This research uses a development approach, or R&D, with a research design that can produce products, use research that needs analysis, and test the product's feasibility so that it can function for the wider community. Research is needed to test the effectiveness of products, namely flip chart learning media (smart pocket books), and active learning of grade V elementary school students. Two experts, a media expert, and a materials expert, validated the study's findings. The media on the flip chart card got a score (3) from a media expert or 92.3%, and a score (4) from a material expert, or 94.5%. All three numbers appear with an average value of 5. Based on the acquisition of this score, it can show that the learning media of the flip chart card (smart pocket book) developed is worthy of being used for trials as development of conventional learning media in the form of flip chart media.